2013
DOI: 10.1021/jo402178r
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the Spiroiminal Moiety and Approaches to the Synthesis of Marineosins A and B

Abstract: A short and efficient synthesis of model spiroiminals that have the same stereochemistry but different conformations than marineosins A and B was carried out in 6-7 steps from 6-methyltetrahydropyran-2-one. These spiroiminals were also prepared biomimetically by reduction of an enol ether. A more highly substituted spiroiminal with the same stereochemistry and conformation as marineosin A was prepared in 11 steps from 6-methyl-4-propyl-3-phenyltetrahydropyran-2-one. A macrocyclic pyrrole lactone was prepared s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Based on unsuccessful synthetic attempts (with the exception of individual key motifs) of several research groups [ 101 , 102 , 103 , 104 , 105 , 106 ], Shi and co-workers presented the first total synthesis of marineosin A ( 85a ) in 2016 [ 107 ]. The synthesis commenced with the commercially available (S)-pyrone 89 , which was converted into key fragment 90 in 10% yield over 14 steps.…”
Section: Non-halogenated Marine Pyrrole Alkaloidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on unsuccessful synthetic attempts (with the exception of individual key motifs) of several research groups [ 101 , 102 , 103 , 104 , 105 , 106 ], Shi and co-workers presented the first total synthesis of marineosin A ( 85a ) in 2016 [ 107 ]. The synthesis commenced with the commercially available (S)-pyrone 89 , which was converted into key fragment 90 in 10% yield over 14 steps.…”
Section: Non-halogenated Marine Pyrrole Alkaloidsmentioning
confidence: 99%
“…This strategy yields several other prodiginine derivatives and premarineosin analogs that show promising cytotoxic and antimalarial activities [100]. Based on unsuccessful synthetic attempts (with the exception of individual key motifs) of several research groups [101][102][103][104][105][106], Shi and co-workers presented the first total synthesis of marineosin A (85a) in 2016 [107]. The synthesis commenced with the commercially available (S)-pyrone 89, which was converted into key fragment 90 in 10% yield over 14 steps.…”
Section: Simple Pyrrolesmentioning
confidence: 99%
See 1 more Smart Citation
“…The LB addition then affords an iodine(III)-enolate species that could be an ideal rearrangement precursor. Subsequent [3,3]-rearrangement and β-elimination take place, nally producing valuable α-aryl α,β-unsaturated carbonyls that have signi cant utility in chemical synthesis [29][30][31][32][33] but may be di cult to make with E/Z selectivity through other known methods [34][35][36] . It should be noted that, while our study was underway, Wengryniuk reported an elegant iodonio-Claisen rearrangement of β-pyridinium silyl enol ethers that allows for α-arylation of α,β-unsaturated ketones.…”
Section: Introductionmentioning
confidence: 99%
“…They are often alternatively accessed through cross-coupling on the corresponding vinyl halide derivatives or through bromination/elimination sequences. 34,35 It worth noting that while comparing EDD with other precedented methods, the set of conditions reported by the Newhouse group was found to provide the desaturated -aryl lactones in moderate yields. Next, the particularly difficult class of aldehydes were investigated (32-34, silyl enol ethers employed).…”
mentioning
confidence: 97%